Percutaneous Angioplasty Used to Manage Native and Recurrent Coarctation of the Aorta in Infants Younger than 1 Year: Immediate and Midterm Results - ADJAGBA, MAHOUNA PHILIPPE DOTOU; Hanna, Baher; Miro, Joaquim; Dancea, Adrian; Poirier, Nancy; Vobecky, Suzanne; Déry, Julie; Lapierre, Chantale; Dahdah, Nagib (My University, 2014)
Balloon angioplasty (BAP) used to manage native coarctation of the aorta (CoAo) in infants remains controversial. This study aimed to compare short- and midterm results of BAP between native CoAo (NaCo) and postsurgical recoarctations (ReCo) in infants younger than 1 year. This retrospective study compared the clinical, echocardiographic, hemodynamic, and angiographic data for infants who underwent BAP between July 2003 and September 2012. The 12 NaCo and 13 ReCo patients in thisstudy underwent BAP at 4.61 ± 3.69 and 4.88 ± 3.07 months (p = 0.84) and weighed 5.49 ± 2.57 and 6.10 ± 2.11 kg (p = 0.52), respectively. Their respective heights were 60.58 ± 10.58 and 61.15 ± 6.74 cm (p = 0.87). All the ReCo patients had their initial surgery before the age of 3 months. The minimal CoAo diameter was 2.81 ± 0.96 mm in the NaCo group and 2.86 ± 1.0 mm in the ReCo group (p = 0.90). The relative gradient reduction was 62.79 ± 32.43 % in the NaCo group and 73.37 ± 20.78 % in the ReCo group (p = 0.33). The in situ complication rate (pseudoaneurysm) was 8.33 % in the NaCo group and 7.69 % in the ReCo group (p = 0.74). During the early follow-up evaluation, five NaCo patients (41.66 %) presented with recoarctation requiring BAP reintervention within 1.75 ± 1.41 months (all had their initial BAP before 3 months of age) compared with 1 ReCo patient (7.69 %) (p = 0.165). The mean follow-up period was 3.09 ± 2.69 years for the NaCo patients and 3.6 ± 3.18 years for the ReCo patients (p = 0.69), during which the blood pressure gradient was 12.33 ± 9.67 for the NaCo patients and 7.80 ± 8.78 for the ReCo patients (p = 0.17), with corresponding Doppler peak instantaneous gradients of 21.29 ± 11.19 and 16.20 ± 10.23 (p = 0.24). The resultant diameter ratio between the minimal isthmus diameter and the aortic diameter at the diaphragmatic level was 0.81 ± 0.15 in the NaCo group and 0.85 ± 0.12 in the ReCo group (p = 0.53). The immediate and midterm results of BAP for the NaCo and ReCo infants were comparable. Accordingly, BAP seems to be an acceptable alternative to surgery for infants older than 3 months.
Keywords: Percutaneous angioplasty; Coarctation of the; aorta; Balloon angioplasty; Postsurgical recoarctations; Native recoarctations